Physics Multimedia Learning (PsML) to Improve Critical Thinking Skills in Distance Learning - Qisthi Fariyani; Laily Zakiyatul Miskiyah (At-Taqaddum, 2022)
The Covid-19 pandemic has caused changes in various sectors, including the education sector. These changes are found in implementing learning that previously took place in the classroom offline and must now be carried out online/blended learning. This study aims to develop a Physics Multimedia Learning (PsML), to test the product's validity and effectiveness in improving pre-service physics teachers' critical thinking skills on the subject of Static Electricity. This study uses a 4D development model. Data collection methods used are questionnaires, tests, and documentation. Validity testing is carried out through an assessment by two experts. The product that has been made is tested on pre-service physics teachers. The sample was taken using a purposive sampling technique by taking pre-service physics teachers who have taken the Basic Physics 1 course. The final product of Physics Multimedia Learning (PsML) contains covers, instructions for use, lists of materials and manuals, apperceptions, material content consisting of videos and pdf materials, activities, questions to make pre-service physics teachers think critically in finding concepts, Quiz, and the final project. The validator's assessment results show that the product is feasible in the excellent category. The experimental class's improvement of critical thinking skills is in the medium type, with a coefficient of 0.6. This increase was higher than the control class, which experienced an expansion with a coefficient of 0.32. Based on the results of data analysis, it can be concluded that PsML is effective for improving critical thinking skills in Static Electricity material.